Pengembangan instrumen penilaian sikap sosial pada pembelajaran tematik sub tema aku anak mandiri kelas IV sekolah dasar - Tomo Sutomo (Universitas Sebelas Maret, 2022)
The formation of students' social attitudes in thematic learning needs to be supported by quality assessment instruments. The purpose of this study is to (1) identify social attitudes in learning, (2) develop a social attitude assessment scale in learning, and (3) analyze the validity and reliability of the instrument. assessment of developed social attitudes. The study used the Research and Development (RnD) method. The research was carried out in Daerah Binaan IV Disdikbuk Muntilan District in the odd semester of the 2021/2022 academic year. The population in this study were 4th grade students of SD Daerah Binaan IV in the area of Desdikbud, Muntilan District. The sample used is grade 4 students at Daerah Binaan IV. The sampling technique used purposive sampling as many as 100 samples, namely the class that carried out observation activities in the thematic learning of the Let's Love the Environment sub theme. The data taken are the assessment instrument model for SD Daerah Binaan IV, the quality of the social attitude assessment scale developed rationally, and empirically. Internal consistency analysis of items was performed using IBM Statistics SPSS 21.0 for Windows. The results obtained are the product in the form of an honest, disciplined, hard-working and independent social attitude assessment scale. Likert scale model meets the criteria for being rationally and empirically feasible, the results of the validity test show that from 20 statements there is one statement that is rejected, namely statement number 6 because of the r value. the count is smaller than 0.195, which is 0.116, 20 items are declared reliable with -Cronbach 0.815 above the minimum standard of 0.6. Based on the results and discussion, it can be concluded that the social attitude assessment instrument developed is suitable for use in thematic learning, especially the Let's Love the Environment Sub-theme in Daerah Binaan IV Disdikbud Muntilan District.